A direct comparison of women's perceptions and acceptability of micronised progesterone and medroxyprogesterone acetate in combination with transdermal oestradiol in the management of young postmenopausal women, under 45 years of age. Issue 4 (December 2020) - Mittal, M; Panay, N; Supramaniam, PR; Savvas, M; Cardozo, L; Hamoda, H
Objective: To assess the acceptability and perception of postmenopausal women, to two different hormone replacement therapy regimens, in relation to the control of their symptoms and development of adverse effects. Study design: Prospectively recruited postmenopausal women, <45 years, were randomised to one of two treatment arms for 12-months: cyclical micronised progesterone or medroxyprogesterone acetate in combination with transdermal oestradiol. A self-reported questionnaire with matrix rating scales was completed and repeated after 3, 6 and 12-months. Main outcome measures: Symptom control and development of adverse effects. Results: Seventy-one individuals were screened, with baseline data available for 67 subjects. A total of 190 questionnaires were returned. The most commonly reported symptoms were low energy levels, vasomotor symptoms and sexual dysfunction. The prevalence of adverse effects ranged between 57.89 and 87.50%, with a reduction seen in the transdermal oestradiol + micronised progesterone arm (73.91% at 3-months, decreasing to 57.89% at 12-months; p = 0.33), compared to the transdermal oestradiol + medroxyprogesterone acetate arm (76.92% at 3-months, increasing to 87.50% at 12-months; p = 0.69). The main reported adverse effects were bloating, weight change and psychological symptoms. A significant difference was documented between the groups after set intervals, with a greater proportion reporting breast tenderness after 3-months (p = 0.01), lower numbers reporting mood swings at 6-months (p = 0.01) and irritability at 12-months (p = 0.03) in the transdermal oestradiol + micronised progesterone arm compared to the transdermal oestradiol + medroxyprogesterone acetate arm. Conclusions: The acceptability of both regimens was high despite adverse effects, but tolerability of transdermal oestradiol combined with micronised progesterone appeared to be better with fewer women reporting psychological concerns.